Youth Violence and Resilience: Approaches to Strategy in the School Environment and Social Policy - Tohari, Mohammad Amin; Sokhivah, Sokhivah (Jurnal Kebijakan Publik, 2025)
This study investigates strategies for addressing adolescent violence within school environments and through social policy interventions in Jakarta, Indonesia. Employing a qualitative design, data were collected through in-depth interviews with 25 informants, comprising teachers, principals, students, and parents, selected via purposive sampling. Data validation was ensured through triangulation of sources, member checking, and peer debriefing. Findings reveal that while national policies—such as the Child-Friendly School (CFS) framework—provide an essential normative foundation, their implementation varies significantly across schools, resulting in uneven protection outcomes. Schools with robust participatory mechanisms and restorative practices demonstrated higher levels of student resilience and reduced incidents of peer aggression. Conversely, institutions lacking inclusive structures often reinforced vulnerability. The analysis integrates the effectiveness framework of Kettner, Moroney, and Martin, highlighting limitations in accountability and systemic coordination. The study concludes by offering actionable policy recommendations, including mandatory school-level monitoring mechanisms, integration of digital reporting tools, and stronger cross-sector collaboration.